PENERAPAN TEORI KONSTRUKTIVIS DALAM PEMBELAJARAN - Fatimah Saguni (Paedagogia: Jurnal Pendidikan, 2019)
Constructivism is the basis for thinking of a contextual approach, namely that knowledge is built not a set of facts, concepts, or rules that are ready to be remembered. Students must construct that knowledge and give meaning through real experience. Students need to be accustomed to solving problems, finding something useful for themselves, and struggling with ideas. The teacher will not be able to give all knowledge to students. Students must construct knowledge in their own minds. Knowledge is not static, but is constantly evolving and changing as students construct new experiences that force them to base themselves and modify previous knowledge.Learning must be packaged into the process of constructing knowledge rather than receiving knowledge. In the learning process, students build their own knowledge through active involvement in the learning and teaching process. Students become the center of activities, not teachers.Critical thinking is an attempt by someone to check the truth of information using the availability of evidence, logic, and awareness of bias. Critical thinking skills are the cognitive processes of students in analyzing systematically and specifically the problems faced, distinguishing these problems carefully and thoroughly, as well as identifying and reviewing information to plan problem solving strategies.